Quadro editorial (Estudos em Design, 2023)
Editores Cristina PortugalRita Maria de Souza CoutoAvaliadores desta edição v. 31Adriana GralowAdriana MirandaAlexandre FarbiarzAlexandre OliveiraÁlvaro SousaAna BerwangerAna PazminoAngelica AdverseAntonio ColcheteBeany MonteiroCarlo FranzatoCayley GuimaraesChrystianne IvanóskiClice MazzilliCyntia Malaguti de SousaDeborah ChristoEdson RufinoEva Rolim MirandaFrederico BraidaGabriel PatrocinioGabriela CarneiroJade PiaiaKátia Carvalhaes PêgoKlaus AlbertoLuiz AgnerMadalena GrimaldiMarcelo BezerraMarcelo ForcatoMarcio GuimarãesMaria Do Carmo Gonçalves CurtisMariana Fonseca BragaMarina KunstMariano Lopes de Andrade Neto Matheus CezarottoNelson KuwaharaOlavo NetoPaula Piva LinkeRafaella PeresRanielder de FreitasRavi PassosRenata CadenaRenata WanderleyRogério CamaraSandra Maria SouzaSérgio Luciano da SilvaWagner BandeiraVagner GodóiVera DamazioViviane Nunes